Experimental investigation on mechanical properties of jute fiber reinforced concrete under freeze-thaw conditions for pavement applications. (14th March 2022) - Affan, Muhammad; Ali, Majid
Highlights: Effectiveness of jute fibers in concrete is explored against freeze-thaw conditions. Voids propagation after different cycles and different properties are studied. Jute fibers can reduce freeze-thaw effects in concrete. Effect of freeze-thaw cycles on both PC and JFRC are examined through SEM. JFRC pavements are likely to have same results with reduced thickness. Abstract: Freeze-thaw is one of the major hazards, which concrete pavements have to experience due to fluctuation in sessional temperatures. Certain measures should be made at the time of construction to prevent concrete pavements from the freeze-thaw deterioration. The use of natural fibers is one such interesting option and jute fibers are selected to explore first due to their local availability. In this work, the effect of different freeze thaw cylces on dynamic and mechanical behavior of plain and jute fiber reinforced concrete is studied. Cracks propagation, loss in mass and relative dynamic modulus, dynamic (i.e. damping ratio and fundamental frequencies) and mechanical (i.e. compressive, split tensile and flexural) properties are considered. To observe the behaviour of freeze-thaw cycles on PC and JFRC, small pieces are further analysed with the help of scanning electron microscope (SEM). Empirical equations are also developed to predict pavement design relevant strengths based on fiber addition and number of freeze thaw cycles. The outcomes of jute fiber reinforced concrete seem favourable for the application of rigid pavement under freeze thaw conditions.